RLNC in satellite networks: A cooperative scenario for delivering M2M traffic. (31st August 2017) - Bacco, Manlio; Gotta, Alberto
Summary: The fraction of machine‐to‐machine traffic carried by satellite networks is increasing, and an efficient delivery is required in order to enable a large set of applications that can benefit from the advantages provided by the use of satellites. This work analyses the use of random linear network coding techniques in land mobile satellite channels to reliably deliver machine‐to‐machine traffic to mobile nodes in urban areas. The considered scenario takes into account a cooperative coverage extension in land mobile satellite vehicular networks, where the use of random linear network coding techniques can remove the need for any fixed equipment on the ground at least in urban environments, where the density of mobile nodes is typically high. Abstract : This work analyses the use of random linear network coding in land mobile satellite channels to deliver M2M messages to vehicles in urban areas. The considered scenario takes into account a cooperative coverage extension among the on board units via 802.11p, where the use of random linear network coding makes negligible the need for any complementary ground components, such as a road side unit, at least in urban environments, where the density of mobile nodes is typically high.